Answer:
7 = -x^2 +16
x^2 -16 = 7
x^2 -23 = 0
Using quadratic equation
x = -0 +- sqrt (23^2 - 4*1*23) / 2 * 1
x = sqrt (0 - -92) / 2
x = sqrt (92) / 2
x1 = 4.7958
x2 = -4.7958
(I tried to answer your question - even though you posted no question - AND you posted no graphics)
Step-by-step explanation:
Answer:
x=-2
Step-by-step explanation:
4x-1=3x-3
x=-2
First bring 3x to the other side, which will give you -2y= -16-3y. Then divide everything by -2, which will give you y=8+3/2x
Answer: At the end of the year, Lorenzo will have $406
Step-by-step explanation:
<h3>400 × .015 = 6. </h3><h3>6 + 400 = 406. </h3>